2019
DOI: 10.1038/s41598-019-50372-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of vertebrate vision in a 384-well imaging system

Abstract: Visual impairment affects 253 million people worldwide and new approaches for prevention and treatment are urgently needed. While small molecules with potential beneficial effects can be examined in various model systems, the in vivo evaluation of visual function remains a challenge. The current study introduces a novel imaging system for measuring visually-guided behaviors in larval zebrafish. The imaging system is the first to image four 96-well plates with a single camera for automated measurements of activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…The fish are fed daily with Gemma Micro 300 and frozen brine shrimp. Zebrafish embryos were collected and grown to larval stages as previously described 18 , 19 . Zebrafish embryos from 0–3 days post-fertilization (dpf) and zebrafish larvae from 3–5 dpf were maintained at 28.5 °C in 2L culture trays with egg water, containing 60 mg/L sea salt (Instant Ocean) and 0.25 mg/L methylene blue in deionized water (pH 7.2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fish are fed daily with Gemma Micro 300 and frozen brine shrimp. Zebrafish embryos were collected and grown to larval stages as previously described 18 , 19 . Zebrafish embryos from 0–3 days post-fertilization (dpf) and zebrafish larvae from 3–5 dpf were maintained at 28.5 °C in 2L culture trays with egg water, containing 60 mg/L sea salt (Instant Ocean) and 0.25 mg/L methylene blue in deionized water (pH 7.2).…”
Section: Methodsmentioning
confidence: 99%
“…The experiments were designed to use the minimum number of zebrafish larvae needed for an evaluation of multiple behaviors. Sample size was determined a priori, based on analyses of behavior in prior studies 19 , 26 . We decided on 190 drugs, using 48 larvae for each pharmacological treatment (n = 48 larvae per drug).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter technique can be conducted in high-throughput fashion using 384-well plates. 114 Using OMR, it was recently demonstrated for zebrafish, as has been shown for mouse, 123 that dynamic visual experience is required for the proper stratification of retinal layers in early eye maturation. 124 Studies have shown that the OMR displayed by larval zebrafish is lost around 16 dpf and that adult zebrafish rely mainly on mechanosensory stimuli via the lateral line for sensing movement, and on positive rheotaxis (defined as the tendency to turn to face into an oncoming current) for maintaining position in flowing water.…”
Section: Functional Vision Testingmentioning
confidence: 99%
“…88 This can be done quantitatively and in high-throughput fashion using larval zebrafish. 113,114 Several behavioral responses to visual stimuli, described below, have been characterized, including optomotor response (OMR), optokinetic response (OKR), visual startle, and visual motor response (VSR and VMR, respectively). These behavioral responses have been used in toxicology as well as in studies designed to discover what types of visual cues play a role in driving behavior, 115,116 genes involved in vision and vision disorders, [117][118][119] and by using in vivo functional imaging, which neurons/circuits are involved in perceiving visual stimuli and eliciting the behavioral response.…”
Section: Functional Vision Testingmentioning
confidence: 99%